Droit foncier et pastoralisme, entre propriété et territoire - Olivier Barrière (Éditions en environnement VertigO, 2017)
Based on French situations we question the place of the pastoral system in the territory and in the law through what defines "pastoral land."How land tenure is dealt with, throughout History, by positive law? How public policies take into account land rights related to pastoralism? These questions lead to a finding. Going further leads us to focus on pastoral land tenure and its implementation combining ownership relationship and territorial relationship. Indeed, the way law grabs pastoral space allows us to question land tenure (legal relationship to land) within the matter of territorial identity (making territory). The paradigm that underlies each of them is not always the same causing tensions or confrontations related to two ways of thinking land.Consideration of both land ownership and reality of "land territory" of the pastoral system leads us to a cross between two paradigms. This question gets particularly acute in the context of the World Heritage listing UNESCO of Causses-Cévennes site for its agro-pastoral landscapes. The switch to local heritage character can not be decreed and this UNESCO inscription lays as an opportunity for local actors to formalize land values around pastoralism. Also, endogenous innovations are being recently promoted by local actors in a process of experimentation within the Community of Communes "Causses Aigoual Cévennes Terres Solidaires" (solidarity Lands). The challenge is to highlight the plurality of relationship to land, private property or common territory, that is not limited to the ontology of ownership.